Habitat heterogeneity and connectivity shape microbial communities in South American peatlands - Oloo, Felix (Sci Rep, 2016)
Bacteria play critical roles in peatland ecosystems. However, very little is known of how habitat heterogeneity affects the structure of the bacterial communities in these ecosystems. Here, we used amplicon sequencing of the 16S rRNA and nifH genes to investigate phylogenetic diversity and bacterial community composition in three different sub-Antarctic peat bog aquatic habitats: Sphagnum magellanicum interstitial water, and water from vegetated and non-vegetated pools. Total and putative nitrogen-fixing bacterial communities from Sphagnum interstitial water differed significantly from vegetated and non-vegetated pool communities (which were colonized by the same bacterial populations), probably as a result of differences in water chemistry and biotic interactions. Total bacterial communities from pools contained typically aquatic taxa, and were more dissimilar in composition and less species rich than those from Sphagnum interstitial waters (which were enriched in taxa typically from soils), probably reflecting the reduced connectivity between the former habitats. These results show that bacterial communities in peatland water habitats are highly diverse and structured by multiple concurrent factors.